2021
DOI: 10.3803/enm.2021.1061
|View full text |Cite
|
Sign up to set email alerts
|

Normocalcemic Primary Hyperparathyroidism: Need for a Standardized Clinical Approach

Abstract: Since normocalcemic primary hyperparathyroidism (NHPT) was first defined at the Third International Workshop on the Management of Asymptomatic Primary Hyperparathyroidism in 2008, many papers have been published describing its prevalence and possible complications. Guidelines for the management of this condition are still lacking, and making the diagnosis requires fulfillment of strict criteria. Recent studies have shown that intermittent oscillations of serum calcium just below and slightly above the normal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Over an 8-year follow-up of 64 subjects identified through community screening, only 1 person developed hypercalcemic PHPT, and only 13 retained the biochemical findings of normocalcemic PHPT (61). Published series have used inconsistent definitions of normocalcemic PHPT and it is thus difficult to estimate the true prevalence and complication rate (62). Reported complication rates vary from zero in population-based studies (63,64,65) to 11-35% of patients with renal stones and 5-40% with lowtraumatic fractures and osteoporosis, as assessed in tertiary referral centers (60,66,67,68,69).…”
Section: Q4 What Are the Manifestations Of Normocalcemic Phpt And Doe...mentioning
confidence: 99%
“…Over an 8-year follow-up of 64 subjects identified through community screening, only 1 person developed hypercalcemic PHPT, and only 13 retained the biochemical findings of normocalcemic PHPT (61). Published series have used inconsistent definitions of normocalcemic PHPT and it is thus difficult to estimate the true prevalence and complication rate (62). Reported complication rates vary from zero in population-based studies (63,64,65) to 11-35% of patients with renal stones and 5-40% with lowtraumatic fractures and osteoporosis, as assessed in tertiary referral centers (60,66,67,68,69).…”
Section: Q4 What Are the Manifestations Of Normocalcemic Phpt And Doe...mentioning
confidence: 99%
“…Due to advances in diagnostics, the clinical presentation of PHPT evolved in developed countries from a symptomatic to an incidentally discovered and asymptomatic disorder [ 47 ]. Recent observational studies suggested that excessive PTH secretion in normocalcemic PHPT, the first subclinical phase of PHPT, might exhibit metabolic disturbances and induce the risks of cardiovascular diseases and tissue dysfunctions [ 48 , 49 ].…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%
“…Nutritional rickets is still endemic in many countries and occurs due to calcium or vitamin D deficiency. Vitamin D supplementation for all infants and young children significantly reduced the incidence of nutritional rickets in Europe and North America [ 48 ].…”
Section: Calcium Deficiencymentioning
confidence: 99%
“…Although the clinical presentation of PHPT is highly variable, asymptomatic hypercalcemia detected incidentally is the most common presentation [ 2 ]. Normocalcemic primary hyperparathyroidism (NHPT) is a newly defined variant of PHPT which has led to new questions regarding its diagnosis and management [ 3 ]. In contrast to PHPT, NPHP is characterised by consistently normal total and ionised calcium (Ca) levels with elevated PTH in the absence of secondary causes of hyperparathyroidism [ 4 ].…”
Section: Introductionmentioning
confidence: 99%